2015
DOI: 10.1088/0004-637x/809/1/50
|View full text |Cite
|
Sign up to set email alerts
|

THE X-RAY LINE FEATURE AT 3.5 KeV IN GALAXY CLUSTER SPECTRA

Abstract: Recent work by Bulbul et al. and Boyarsky et al. has suggested that a line feature at ∼3.5 keV in the X-ray spectra of galaxy clusters and individual galaxies seen with XMM-Newton is due to the decay of sterile neutrinos, a dark matter candidate. This identification has been criticized by Jeltema & Profumo on the grounds that model spectra suggest that atomic transitions in helium-like potassium (K XVIII) and chlorine (Cl XVI) are more likely to be the emitters. Here it is pointed out that the K XVIII lines h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Ref. [632] analyze high-resolution solar flare spectra and find that the coronal potassium abundance is a factor of 9-11 higher than the photospheric abundances assumed in the above analyzes, offering a explanation as to why the flux of these lines may be brighter than expected. It is, however, not clear why the solar corona should exhibit similar isotopic abundances to the IGM, as the metallicity is generally expected to be higher near stars.…”
Section: 5 Kev Linementioning
confidence: 88%
See 1 more Smart Citation
“…Ref. [632] analyze high-resolution solar flare spectra and find that the coronal potassium abundance is a factor of 9-11 higher than the photospheric abundances assumed in the above analyzes, offering a explanation as to why the flux of these lines may be brighter than expected. It is, however, not clear why the solar corona should exhibit similar isotopic abundances to the IGM, as the metallicity is generally expected to be higher near stars.…”
Section: 5 Kev Linementioning
confidence: 88%
“…More recently, two papers have argued for potential astrophysical origins in the 3.5 keV line [632,633]. Ref.…”
Section: 5 Kev Linementioning
confidence: 99%
“…First of all, the excess has not been found in dwarf galaxy observations [46][47][48][49]. Furthermore, it was argued that the signal could arise due to an incomplete subtraction of atomic lines [50,51] and that it does not have the right morphology expected by the DM profile [52,53] (although both criticisms have been challenged as well [54,55]). Currently, it seems very hard to draw definite conclusions from the status of the emission line, as poor statistics leave room for interpretation.…”
Section: The 355 Kev Line Signalmentioning
confidence: 99%
“…A photospheric argon abundance is expected if the low-FIP elements are enhanced in the corona. Recently, Phillips et al (2015) found very high potassium abundances in flares, which impact the interpretation of galaxy cluster spectra. This emphasizes the importance of solar abundance variations to astrophysics in general.…”
Section: Introductionmentioning
confidence: 99%